Adobe Illustrator Classroom in a book (2020 release) : the official training workbook from Adobe - Wood, Brian (Adobe instructor) (Classroom in a book., 2020)
The fastest, easiest, most comprehensive way to learn. The best-selling series of hands-on software training workbooks, offers what no other book or training program does--an official training series from Adobe, developed with the support of Adobe product experts. Contains 16 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Build a strong foundation by following hands-on projects for creating logos, illustrations, and posters. Learn how to use the Shaper tool and Live Shapes along with dynamic symbols to streamline graphics creation. Create website assets and export them in multiple formats to support modern responsive web designs. From exacting illustration to more free-form painting, you'll gain vital skills as you progress through the lessons. The online companion files include all the necessary assets for readers to complete the projects featured in each chapter. All buyers of the book get full access to the Web Edition: A Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.